Konfirmatori Model Responsible Environmental Behavior (REB) pada Mahasiswa di Kota Bukittinggi: Sebuah Analisis Geografi Perilaku - Fatria, Erian; Priadi , Agus; Apriyanti, Eka (GEOGRAPHIA : Jurnal Pendidikan dan Penelitian Geografi, 2025)
Environmentally irresponsible behavior has led to a deterioration in environmental quality. This study aims to obtain confirmation related to environmentally responsible behavior based on attitudes in coping with climate change disasters and the desire to maintain environmental health. The method in this study is a quantitative method involving 47 students in Bukittinggi City, who were selected by multistage random sampling. The results showed that students' environmental responsible behavior was influenced by attitudes in coping with climate change disasters and the desire to maintain environmental health very significantly, meaning that if you want better environmental responsible behavior, it is necessary to consider the influence of variations in attitude and intention to act on the basis of empirical findings model.